Wpływ gospodarki opartej na układach sieciowych na rozwój innowacyjności - Czetwertyński, Sławomir (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article discusses relations between network based economy and processes that create innovations. The first part of the paper characterizes innovation's process and presents two different models describing arising new solutions and technologies. The first model is based on linear theory and the second one on the evolution and adapting of theoretical knowledge in to practical solutions. The next part describes network based economy and the profits of it to the entrepreneurs. The analytic part of this paper draws a parallel between profits coming from network based economy and nonlinear innovation's model. In the conclusion there are arguments to the strong connection between innovation and development of the network economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 72-81